Children, citizenship and crisis: towards a participatory agenda - Almeida, Ana Nunes de (2018)
Children’s citizenship has become a major theme in contemporary social policy and science debates, and children’s rights have gradually emerged as benchmarks for many national, regional or local policy narratives, consistent with the un Convention on the Rights of the Child (un 1989). Indeed, the uncrc concept of citizenship encompasses, for the first time, participation, provision but also participation rights. The attention has focused not only on children’s “superior interest” but also on their agency capacities and their participatory rights, considering them active and competent actors in social relationships, who have a voice, irrespective of those of adults. Crises, caused by disasters, economic and social adversities are moments of disruption where the pre-existing unequal social ties between individuals or groups in society become more visible, evidencing different access to citizenship status. Children have very often been portrayed as passive and helpless victims or as vulnerable recipients of aid in crisis situations, with little attention given to their ability to perceive and interpret these phenomena, or what they can contribute to public policies that address these issues.